2015
DOI: 10.3899/jrheum.150550
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Milnacipran on Pain in Patients with Rheumatoid Arthritis with Widespread Pain: A Randomized Blinded Crossover Trial

Abstract: Objective Clinical trials have shown that serotonin norepinephrine reuptake inhibitors, such as milnacipran, decrease pain in non-inflammatory pain conditions like fibromyalgia and osteoarthritis. We examined the effect of milnacipran on self-reported pain intensity and experimental pain sensitivity among rheumatoid arthritis (RA) patients with widespread pain and stable RA disease activity. Methods In this double-blind, crossover study, RA patients with widespread pain, on a stable treatment regimen, were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 47 publications
1
21
2
1
Order By: Relevance
“…Similarly, no significant analgesic effect of milnacipran compared with placebo was observed on global pain, and pain diminished similarly in both groups, stressing the lack of efficacy of milnacipran and the strong placebo effect. This lack of analgesic effect is, however, contradictory to previous studies with milnacipran and duloxetine that showed 40 43 , 56 a pain diminution of 30% in 40% patients, a value higher than that in our study (30% diminution in 29% milnacipran group and 25% placebo group, p =0.745). The strong placebo effect observed in FM patients confirms, however, the literature on milnacipran 60 and was also shown for duloxetine and gabapentin.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Similarly, no significant analgesic effect of milnacipran compared with placebo was observed on global pain, and pain diminished similarly in both groups, stressing the lack of efficacy of milnacipran and the strong placebo effect. This lack of analgesic effect is, however, contradictory to previous studies with milnacipran and duloxetine that showed 40 43 , 56 a pain diminution of 30% in 40% patients, a value higher than that in our study (30% diminution in 29% milnacipran group and 25% placebo group, p =0.745). The strong placebo effect observed in FM patients confirms, however, the literature on milnacipran 60 and was also shown for duloxetine and gabapentin.…”
Section: Discussioncontrasting
confidence: 99%
“…Chronic pain and FM are known to have a deleterious influence on cognitivo-emotional domains, affecting emotion, concentration, and memory. 44 , 56 , 63 Our FM sample was cognitively impaired regarding vigilance and memory when compared with non-FM healthy volunteers from a previous study (Corriger et al, unpublished data, 2017). After 1-month treatment with milnacipran, no difference was, however, highlighted between both groups.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…However, using widespread pain alone for selective recruitment of participants was not adequate in a clinical trial of the centrally acting analgesic milnacipran in people with RA, although the number of participants might be small and secondary analysis implicated a confounding effect of synovitis on the pain measurements [42]. Clustering algorithms based on studies such as ours and others [19] represent an alternative tool for determining recruitment criteria for personalised medicine trials.…”
Section: Discussionmentioning
confidence: 99%
“…29 Finally, in a double-blind RCT of milnacipran in patients with rheumatoid arthritis and widespread pain, changes in pressure pain threshold in the placebo group did not correlate with changes in pain intensity at the 6th week of treatment. 30 FM is also associated with impairment of cognitive and executive functions, which is worse in the case of accompanying depressive disorders. 31,32 There are few data about cognitive improvement during therapeutic challenges, and none about the relationship with non-specific pain relief.…”
Section: Discussionmentioning
confidence: 99%